Hyperpolarization-independent maturation and refinement of GABA/glycinergic connections in the auditory brain stem - Lee, Hanmi (J Neurophysiol, 2015)
During development GABA and glycine synapses are initially excitatory before they gradually become inhibitory. This transition is due to a developmental increase in the activity of neuronal potassium-chloride cotransporter 2 (KCC2), which shifts the chloride equilibrium potential (E(Cl)) to values more negative than the resting membrane potential. While the role of early GABA and glycine depolarizations in neuronal development has become increasingly clear, the role of the transition to hyperpolarization in synapse maturation and circuit refinement has remained an open question. Here we investigated this question by examining the maturation and developmental refinement of GABA/glycinergic and glutamatergic synapses in the lateral superior olive (LSO), a binaural auditory brain stem nucleus, in KCC2-knockdown mice, in which GABA and glycine remain depolarizing. We found that many key events in the development of synaptic inputs to the LSO, such as changes in neurotransmitter phenotype, strengthening and elimination of GABA/glycinergic connection, and maturation of glutamatergic synapses, occur undisturbed in KCC2-knockdown mice compared with wild-type mice. These results indicate that maturation of inhibitory and excitatory synapses in the LSO is independent of the GABA and glycine depolarization-to-hyperpolarization transition.